PERAN PERUSAHAAN MULTINASIONAL TERHADAP PERUBAHAN UPAYA PENANGANAN DEFORESTASI BRASIL DI AMAZON - Maria Aurelia Pramitha; Muhammad Faizal Alfian (Journal of International Relations Diponegoro, 2023)
The Amazon are being destroyed every year due to land conversion and fires. Brazil has committed to reduce deforestation rates with various policies. Unfortunately, since Jair Bolsonaro took office as President of Brazil in 2019, the commitment to reduce deforestation of the Amazon has been faded. Commitment shifting is indirectly driven by international trade carried out by multinational corporation, especially multinational corporation which enggaged in the global supply chain for cattle ranching and soybean agriculture, both of these sectors are contribute to the majority of deforestation in the Amazon. This study presents the formulation of the problem is "What is the role of multinational corporation in Brazilian policy changes in the forest management and deforestation of the Amazon?". By using dependency theory, this study argues that Brazil as a developing country is under the shadows of the interests of multinational corporation due to inequality, inevitably the government accommodate these interests in changing policies to expand the expansion of multinational corporation in the Amazon, especially those related to the exploitation of natural resources and deforestation. This research is a qualitative research using descriptive research type. This research finds that inequality in global capitalism brings exploitative development in Brazil, especially to deforestation for commercial land conversion and this condition is accommodated by the Brazilian government under Jair Bolsonaro.